Revealing the Molecular Regulatory Mechanism of Flavonoid Accumulation in Tender Leaves of Tea Plants by Transcriptomic and Metabolomic Analyses - Ruiyang Shan; Yongheng Zhang; Xiaomei You; Xiangrui Kong; Yazhen Zhang; Xinlei Li; Lu Wang; Xinchao Wang; Changsong Chen (Plants)
Flavonoids are secondary metabolites that are beneficial to life activities and are mainly concentrated in buds and leaves in the form of glycosides. Flavonoid glycosides have important effects on the properties and quality of tea plants. Research has shown that the abundance of flavonoid glycosides varies greatly among different cultivars, but research on the regulatory mechanisms that cause their differential accumulation among tea plant cultivars with different leaf colors is lacking. In this study, an integrated analysis of metabolomics and transcriptomics was conducted to determine the regulatory networks regulating astringency and color-related flavonoids in tea plant cultivars with diverse leaf colors. A total of five anthocyanidins, four catechins, and nine flavonol glycosides were found to partially contribute to the differences in taste and leaf color among tea plant cultivars with diverse leaf colors. Furthermore, 15 MYB genes and 5 Dof genes were identified as potential regulators controlling the expression of eight key structural genes, resulting in differences in the accumulation of specific compounds, including epicatechin (EC), catechin (C), cyanidin, cyanidin 3-O-glucoside, pelargonidin 3-O-glucoside, and quercetin 3-O-glucoside, in tea plant cultivars with diverse leaf colors. These findings provide insights into the development and utilization of resources from tea plants with diverse leaf colors.